Body composition of females in two age groups - Zeqiri L.; Shukova Stojmanovska D.; Georgiev G. (My University, 2020)
Studies in a variety of countries have shown increases in the prevalence of overweight among women in recent years. These increases have given rise to concern about women’s health and well-being. The purpose of this paper was to prove the differences in body composition between women aged 19-20 and 21-28 years old, respectively to prove whether the age has an impact on body composition on women. For the realization of the purpose of the work, the sample included 52 women aged 19-28 years. The sample was divided into two groups, Group 1 (N = 25) - Females 19-20 years and Group 2 (N = 27) - Females 21-28 years. The parameters of the body composition applied in this research were: calendar age (age), height of the body (height), body weight (weight), body fat, muscle mass (muscle), daily calorie intake (kcal), metabolic age, total body water (water), internal fat (visceral fat), and body mass index (BMI). The basic statistical and distribution parameters that have been ++applied in this paper are Minimum, Maximum, Mean, Std. Deviation, Skewness, Kurtosis, Max-D and Kolmogorov-Smirnov test (K-S). To verify the difference between the arithmetic averages of the groups, independent samples T-test was applied. The results obtained showed that there were differences in arithmetic averages in all parameters of body composition between group 1, females 19-20 years and group 2, females 21-28 years. However, a significant statistical difference between these two groups has been obtained in the metabolic age variable, which shows that from the age of 21, women begin a decrease in daily physical movements.
Keywords: obesity, body composition, women, T-test